Pengembangan Media Pembelajaran Gamifikasi Berbasis Quizizz untuk Meningkatkan Motivasi Belajar Peserta Didik - Willy Akmansyah Lubis (An-Nuha, 2026)
This study aims to increase student motivation after the implementation of gamification learning media based on Quizizz. Gamification-based learning media using the Quizizz application will be tested at MTs Mardiyah Islamiyah Panyabungan. The method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The trial was conducted in the context of learning Akidah Akhlak for class VIII students in the odd semester of the current academic year. The trial subjects consisted of 12 class VIII students of MTs Mardiyah Islamiyah Panyabungan. Based on the results of the development and implementation of gamification-based learning media using the Quizizz application, it can be concluded that this media is able to increase the learning motivation of class VIII students in the Akidah Akhlak subject at MTs Mardiyah Islamiyah Panyabungan. The results of the questionnaire showed that the majority of students responded positively to the use of Quizizz. They felt more motivated, focused, confident, and satisfied with the learning process.